Pengaruh Investasi, Tenaga Kerja, dan Produksi Perikanan Terhadap Pertumbuhan Ekonomi Pulau Jawa - Agnes Widyastuti; Jaka Nugraha (Jurnal Ekonomika : INDEPENDEN, 2021)
The success of economic growth is inseparable from influencing indicators, includinginvestment, labor, and fishery production. This indicator is needed in order to boost thevalue of stable economic growth in the framework of long-term sustainable economicdevelopment. The point of research is to prove the effect of investment, labor, and fisheryproduction variables on the economic growth of the island of Java in the 2015-2019period partially. The data source used is secondary data using saturated samplingtechnique. The type of data is panel data consisting of 6 provinces and a time span of 5years. The research approach used is a descriptive quantitative approach that is analyzedwith linear regression analysis of panel data with the help of the program Eviews 10.This research shows that partially investment has a significant positive effect oneconomic growth, labor has a significant negative effect on economic growth. Fisheriesproduction has a significant positive effect on economic growth. Keywords: Economic Growth, Investment, Labor, Fishery Production.